Global value chains, the anti-globalization backlash, and EU trade policy: a research agenda. Issue 6 (2nd June 2020) - Dür, Andreas; Eckhardt, Jappe; Poletti, Arlo
ABSTRACT: Two recent developments have the potential to fundamentally alter the conventional view of EU trade policy-making: the emergence of global value chains (GVCs) and the recent backlash against globalization. In this paper we summarize the conventional wisdom after which we delineate the main expectations derived from the GVC and the globalization-backlash perspectives. In so doing, we focus on the EU's trade and non-trade preferences, and the EU's ability to achieve its preferences in international trade negotiations. We then discuss the research agenda that would allow testing the expectations derived from these different perspectives. A key point that emerges from this discussion is that the conventional perspective, the GVC perspective, and the globalization-backlash perspective may all be needed to fully understand EU trade policy. The challenge is to know under which conditions which of these perspectives best explains the process and outcomes of EU trade policy-making.